An Experimental Test of Defenses Against Avian Brood Parasitism in a Recent Host - Abernathy, Virginia E.; Johnson, Laura E.; Langmore, Naomi E. (Frontiers in Ecology and Evolution, 2021)
Theoretical studies predict that hosts of avian brood parasites should evolve defenses against parasitism in a matter of decades. However, opportunities to test these predictions are limited because brood parasites rarely switch to naïve hosts. Here, we capitalize on a recent host switch by the brood-parasitic Pacific Koel (Eudynamys orientalis) in eastern Australia, to investigate how quickly the Red Wattlebird (Anthochaera carunculate), a recent host that has been annexed by the koel within the last 90 years, can learn to recognize and mob adult cuckoos and evolve the ability to eject parasite eggs. Pacific Koel nestlings kill all host young, so there should be strong selection for hosts to evolve defenses. However, low parasitism rates and high egg recognition costs might slow the spread of egg ejection in our study populations, while adult parasite recognition should be able to spread more rapidly, as this defense has been shown to be a learned trait rather than a genetically inherited defense. We tested Red Wattlebirds at two sites where parasitism rate differed. As predicted, we found that the Red Wattlebird showed little or no ability to eject foreign model eggs at either site, whereas two historical hosts showed high levels of egg ejection at both sites. However, Red Wattlebirds responded significantly more aggressively to a koel mount than to mounts of a harmless control and nest predator at the site with the higher parasitism rate and gave significantly more alarm calls overall towards the koel mount. Our results support previous evidence that recognition and mobbing of a brood parasite are learned traits and may be especially beneficial to naïve hosts that have not had enough time or a high enough selection pressure to evolve egg rejection.